Time-series measurements of 234Th in water column and sediment trap samples from the northwestern Mediterranean Sea - Cochran, J. Kirk; Miquel, Juan Carlos; Armstrong, Robert; Fowler, Scott W.; Masqué, Pere; Gasser, Beat; Hirschberg, David; Szlosek, Jennifer; Rodriguez y Baena, Alessia M.; Verdeny, Elisabet; Stewart, Gillian M. (Deep-sea research. Part II, Topical studies in oceanography, 2009)
Disequilibrium between 234Th and 238U in water column profiles has been used to estimate the settling flux of Th (and, by proxy, of particulate organic carbon); yet potentially major non-steady-state influences on 234Th profiles are often not able to be considered in estimations of flux. We have compared temporal series of 234Th distributions in the upper water column at both coastal and deep-water sites in the northwestern Mediterranean Sea to coeval sediment trap records at the same sites. We have used sediment trap records of 234Th fluxes to predict temporal changes in water column 234Th deficits and have compared the predicted deficits to those measured to determine whether the time-evolution of the two coincide. At the coastal site (327 m water depth), trends in the two estimates of water column 234Th deficits are in fairly close agreement over the 1-month deployment during the spring bloom in 1999. In contrast, the pattern of water column 234Th deficits is poorly predicted by sediment trap records at the deep-water site (DYFAMED, ∼2300 m water depth) in both 2003 and 2005. In particular, the transition from a mesotrophic to an oligotrophic system, clearly seen in trap fluxes, is not evident in water column 234Th profiles, which show high-frequency variability. Allowing trapping efficiencies to vary from 100% does not reconcile the differences between trap and water column deficit observations; we conclude that substantial lateral and vertical advective influences must be invoked to account for the differences. Advective influences are potentially greater on 234Th fluxes derived from water column deficits relative to those obtained from traps because the calculation of deficits in open-ocean settings is dominated by the magnitude of the “dissolved” 234Th fraction. For observed current velocities of 5–20 cm s −1, in one radioactive mean-life of 234Th, the water column at the DYFAMED site can reflect 234Th scavenging produced tens to hundreds of kilometers away. In contrast, most of the 234Th flux collected in shallow sediment traps at the DFYFAMED site was in the fraction settling >200 m d −1; in effect the sediment trap can integrate the 234Th flux over distances ∼40-fold less than water column 234Th distributions. In some sense, sediment trap and water column sampling for 234Th provide complementary pictures of 234Th export. However, because the two methods can be dominated by different processes and are subject to different biases, their comparison must be treated with caution.